Scleral buckle surgery for pseudophakic and aphakic retinal detachment in western Nepal - Byanju, RN; Bajimaya, S; Kansakar, I; Melamud, A (Nepalese Journal of Ophthalmology, 2011)
Introduction: Retinal detachment remains one of the most serious complications of cataract surgery. Treatment of this condition has represented a challenge for vitreoretinal surgeons. Scleral buckle (SB) surgery is one of the treatment options in pseudophakic and aphakic retinal detachment (RD). Aims: To find out the anatomical and visual outcome of SB in pseudophakic and aphakic RD. Subjects and methods: Retrospective case series of 46 consecutive eyes of 46 patients with RD (38 pseudophakic and 8 aphakic eyes) that had undergone conventional SB surgery were reviewed from patient files. Postoperative retinal status at 3 weeks, 6 weeks and 3 months were recorded to see the anatomical success rate after retinal reattachment surgery. Best corrected visual acuity (BCVA) at 3 months follow-up was noted. Results: The mean age of the patients was 54.28 ± 13.49 years. Forty eyes (86.9 %) had primary attachment by 6 weeks duration. Five eyes had undergone repeat surgery within a six-week duration (pars plana vitrectomy). Forty patients had follow-up visit to 12 weeks, achieving retinal attachment in 37 eyes (80.5 %). Best corrected visual acuity (BCVA) at 3 months was better than 6/60 in 18 eyes (39.1%), BCVA better or equal to 1/60 but less than 6/60 in 18 eyes (39.1%) and BCVA less than 1/60 in 4 eyes (8.7 %). Conclusion: Conventional scleral buckling has good outcome for pseudophakic and aphakic RD and can be useful for patients in peripheral eye hospitals where patients cannot afford high cost surgeries. Keywords: scleral buckle, pseudophakia, retinal detachment DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5261 Nepal J Ophthalmol 2011; 3(2): 109-117